Gynocentrism: Female Superiority Propaganda in The Woman King - Aris, Qori; Syam, Essy (Universitas Negeri Semarang, 2025)
This study examines how the film The Woman King constructs gynocentric discourse through cinematic narrative strategies. While contemporary cinema increasingly features strong female protagonists, the research gap lies in understanding how historical narratives are selectively reconstructed to naturalize contemporary ideologies of female supremacy. Using John Fiske's three-level semiotic framework (reality, representation, and ideology), this qualitative analysis examines character construction, narrative patterns, and visual representations in the film. Findings reveal that the film employs ideological techniques including historical transfer, selective framing, and testimonial to establish female dominance across physical, intellectual, and moral domains. Critically, the study identifies significant ideological ambivalence: despite systematically constructing narratives of female superiority, the film paradoxically requires patriarchal validation for female achievements, exemplified in the kpojito title conferment scene. This reveals that contemporary gender representation involves complex negotiations between progressive aspirations and persistent androcentric frameworks. The research contributes theoretical insights into how semiotic analysis can expose ideological contradictions within ostensibly progressive media content.